Pengaruh Kepedulian Orang Tua Terhadap Prestasi Siswa Kelas VIII C SMP Muhammadiyah 57 Medan - Amelia, Nisa; Rahmah, Siti; Santana, Syailla Najwa (Journal of Sustainable Education, 2025)
This study aims to analyze the effect of parental concern on student learning achievement outcomes in junior high school. Using a quantitative approach, this study collected data through a survey involving 27 students. The results showed that there is a significant relationship between parental concern and student learning achievement. The variables analyzed include attention to homework, supervision of learning activities outside school, and communication between parents and children regarding education. The findings provide important implications for education policy and raising parents' awareness of their role in supporting their children's academic development.